PREVENTION OF INTOLERANCE THROUGH IMPLEMENTATION OF ISLAMIC COMMUNICATION IN RELIGIOUS MODERATION - Mokhammad Mahfud; Abdul Ghofur; Najahan Musyafak (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
The cases of violence due to religious intolerance occurred in Indonesia. The problem of intolerance disturbs the nationhood and state. It should be handled as early as possible to prevent it from developing into radicalism, extremism, and terrorism. The article discusses the issue of intolerance in Indonesia, particularly in Yogyakarta, and emphasizes the need for the government and society to use Pancasila as a guideline to prevent intolerance. It advocates implementing Islamic communication in religious moderation as a step to counter intolerance. The integration between communication science and Islam is highlighted, focusing on principles of communication and da'wah in the Qur'an. The article cites verses from the Qur'an and quotes various scholars and experts to support its argument. This study used a qualitative descriptive method based on interviews, observations, and documentation results. This study was conducted to see how the prevention of intolerance through the application of Islamic communication as a basis for developing religious moderation in the Office of the Ministry of Religion of Sleman Regency works. The research results shows that the nine principles of Islamic communication are optimized to maintain religious moderation. The research also found that Islamic communication based on the principles of the Qur'an can be an effective tool to promote religious moderation and prevent intolerance in Indonesia. The integration of communication science and Islamic values is seen as essential in achieving harmony and peaceful coexistence among diverse communities.